Augmented Reality Mobile App for Earthquake Preparedness in High School Students - Cortez Benites, Erikc Anderson; Barrios Aedo, Julio Enrique; Rojas Malasquez, Royer Edelwer (LACCEI, 2025)
Earthquakes are natural events that can cause severe damage and loss of life, especially in seismic zones. Education on preparedness and response to these events is crucial, particularly for children and youth. The “Tremor Kid” project proposes an augmented reality mobile application aimed at educating children and young people about earthquake preparedness and response. The application, created with augmented reality technologies such as Unity, Vuforia and ARCore, offers a series of interactive and educational activities guided by a virtual assistant who dynamically explains safety protocols. Users interacted with the images provided by the application that were placed in their environment, learned how to identify safe areas, prepare emergency backpacks and first aid kits, and participated in activities to identify safe locations during an earthquake. To evaluate the effectiveness of the application, a pilot study was conducted with nine students from the “Jesus Reparador” school, applying questionnaires before and after the use of the application. The results of the study showed that users obtained an improvement in earthquake preparedness and response.